Best Answer

Like this. Factor inside the radical.

3sqrt(2^2*2^2 *5)

as you can see....4 *4 = 16 * 5 = 80, so you can bring both 2,s out and multiply them against the 3

2*2*3sqrt(5)

= 12sqrt(5)

simplified

More answers

Lvl 1

21

Q: How do you simplify the radical 3 sqrt 80?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2*sqrt(75) = 2*sqrt(25*3) = 2*sqrt(25)*sqrt(3) = 2*5*sqrt(3) = 10*sqrt(3)

3 sqrt (3)Put the radical where the "sqrt" is with the second 3 inside.

In order to work with radicals (adding or subtracting) they have to have the same radical expression. ex: 2 rad 3 + 4 rad 3 = 6 rad 3. If it helps, change the similar radicals to a variable. 2 rad 3 + 4 rad 3 2 x + 4 x = 6x and then substitute your radical back in for the variable. 6 rad 3 ---- rad 12 - 3 rad 3 Let's simplify radical 12. First, factor 12 into a perfect square, and a not perfect square.) Hint: we want it to be radical 3 to work with it... 3 times what is 12? rad 12 = sqrt(12) = sqrt(4*3) sqrt(4*3) = sqrt(4)*sqrt(3) sqrt(4) is just 2! We bring this to the "outside" of the radical. sqrt(4)*sqrt(3) = 2 sqrt(3) or 2 rad 3 rad 12 - 3 rad 3 2 rad 3 - 3 rad 3 (or 2x - 3x if it helps) We're left with: -1 rad 3, or just - rad 3 (negative radical 3)

sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3

6

Related questions

sqrt(27) = 3*sqrt(3).

2*sqrt(75) = 2*sqrt(25*3) = 2*sqrt(25)*sqrt(3) = 2*5*sqrt(3) = 10*sqrt(3)

Factorise 12.Replace each pair appearing in this factorisation as by the same number outside the radical and then put everything under the radical sign. sqrt(12) = sqrt(2*2*3) = 2*sqrt(3)

You can rationalize the denominator by multiplying this fraction by a fractional form of one in radical form. 3/sqrt(2) * sqrt(2)/sqrt(2) = 3sqrt(2)/2 ----------------

Yes. So 3*sqrt(2) + 5*sqrt(2) = 8*sqrt(2) But you may need to simplify terms eg 3*sqrt(2) + 5*sqrt(8) = 3*sqrt(2) + 10*sqrt(2) = 13*sqrt(2)

If we factor 60, we get 60 = 2 * 2 * 3 * 5 So sqrt ( 60 ) = sqrt (2 * 2 * 3 * 5) = sqrt (2 * 2) * sqrt (3 * 5) = 4 * sqrt( 15 ) ____________________________________________________________ actually if you do by just using the simpler way you should get 2 radical 15 since , 60 has the closest perfect square of 4 and non perfect of 15 this is how you should solve radical 60 = radical 4 times radical 15 radical 60 = simplify the 4 to 2 and leave radical 15 So , radical 60 = 2 radical 15 not what is above .

sqrt(3) x sqrt(15) = sqrt( 3 x 15 ) = sqrt( 45 ) = sqrt( 9 x 5 ) = 3 sqrt(5)

The SQRT(18) in radical form is 3*SQRT(2), where SQRT represents the radical symbol.

3 sqrt(6) x sqrt(6) = 18

You multiply the two fractions, put the result under the radical symbol and simplify, if possible. Then multiply the result by the whole number.For example, sqrt(1/6)*sqrt(3/4)*5 = sqrt[(1/6*3/4)]*5 = sqrt(3/24)*5= sqrt(1/8)*5 = 1/2*sqrt(1/2)*5 = 5/2*sqrt(1/2).You multiply the two fractions, put the result under the radical symbol and simplify, if possible. Then multiply the result by the whole number.For example, sqrt(1/6)*sqrt(3/4)*5 = sqrt[(1/6*3/4)]*5 = sqrt(3/24)*5= sqrt(1/8)*5 = 1/2*sqrt(1/2)*5 = 5/2*sqrt(1/2).You multiply the two fractions, put the result under the radical symbol and simplify, if possible. Then multiply the result by the whole number.For example, sqrt(1/6)*sqrt(3/4)*5 = sqrt[(1/6*3/4)]*5 = sqrt(3/24)*5= sqrt(1/8)*5 = 1/2*sqrt(1/2)*5 = 5/2*sqrt(1/2).You multiply the two fractions, put the result under the radical symbol and simplify, if possible. Then multiply the result by the whole number.For example, sqrt(1/6)*sqrt(3/4)*5 = sqrt[(1/6*3/4)]*5 = sqrt(3/24)*5= sqrt(1/8)*5 = 1/2*sqrt(1/2)*5 = 5/2*sqrt(1/2).

3 sqrt (3)Put the radical where the "sqrt" is with the second 3 inside.

sqrt(27) = sqrt(9*3) = sqrt(9)*sqrt(3) = 3*sqrt(3)